If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 17 = 75 Reorder the terms: 17 + 2x = 75 Solving 17 + 2x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 2x = 75 + -17 Combine like terms: 17 + -17 = 0 0 + 2x = 75 + -17 2x = 75 + -17 Combine like terms: 75 + -17 = 58 2x = 58 Divide each side by '2'. x = 29 Simplifying x = 29
| 3g+20=20g+2 | | 2g+20=20g+2 | | -a=-P+3b+4c | | 3h+3=7h-17 | | 5d+6=4d+12 | | 9/4÷3/8= | | 13c/4d/2c | | 9/4÷3/8 | | 3b-7=5b-23 | | 7x+1-3(x+1)=9x+2 | | 18v^6w^9-12vw^6x^2=0 | | 3(6+2x)=3x+6 | | 7-3(x-2)=7-x(4-4x) | | 57/95=18/x | | (8z-6)=90 | | 2n+3=113 | | 4x+6x+7y+9y= | | 4x+19+3x+2=90 | | 4x+19+3x+2=180 | | 0.3/Q | | -4+12y+9=16+16y-39 | | -80+20=-2x+14x | | (X+2)(x^2+5)= | | k/3-1/2=10 | | 5m-32=2m+118 | | x^2-5x/x-1 | | 3x+24=75 | | 0=x+2+x^2 | | 5x+15+3x+15=180 | | 10=21/4t | | 0=5-12n | | (2x+3y)dy+(y-x)dx=0 |